HUBUNGAN ANTARA SCHOOL WELL-BEING DENGAN PENYESUAIAN DIRI SOSIAL PADA SISWA KELAS XI DI SMA NEGERI 1 TONDANO - Garcia Rahel Kiroyan; Deetje Solang; Meike Endang Hartati (IKIP Siliwangi, 2026)
The school environment influences students’ psychosocial development, particularly their social adjustment. School well-being is related to students’ well-being at school and the way they interact socially. This study aimed to examine the relationship between school well-being and social adjustment among senior high school students. A quantitative approach with a correlational design was employed. The sample consisted of 119 eleventh-grade students at SMA Negeri 1 Tondano selected using probability sampling. Data were collected using a school well-being scale and a social adjustment scale developed based on the Likert scale model. Data were analyzed using Pearson correlation analysis. The results showed a significant positive relationship between school well-being and social adjustment, with a correlation coefficient of 0.804 and a significance value of 0.000 (p < 0.05). These findings indicate that higher levels of school well-being are associated with better social adjustment. Therefore, a school environment that supports school well-being is important for improving students’ social adjustment.